2005
DOI: 10.3748/wjg.v11.i6.797
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of uridine-diphosphoglucuronosyltransferase 1A7 gene in Taiwan Chinese

Abstract: The results indicate that the allele frequencies of UGT1A7 gene in Taiwan Chinese are different from those in Caucasians and Japanese. Carriage of the nucleotide 211- variant UGT1A gene is highly associated with UGT1A7*3. The restriction-enzyme-digestion method for the determination of nucleotides -57 (or 33, or 622) and 387 can rapidly identify genotypes of UGT1A7 in an individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…Very recently, we found that Taiwanese differed from Caucasians and Japanese with respect to the allele frequencies of the UGT1A7 gene and the UGT1A7 * 4 (Asn 129 Arg 131 Arg 208 ) allele, with 0.017 in frequency in Caucasians (15), was not detected in our study subjects (21). We also observed that the functional polymorphisms at nucleotide 387 (T to G) (Asn 129 Lys) was associated with SNPs at nucleotides 391 (C to A) (Arg 131 Lys) and 392 (G to A) (Arg 131 Lys) in one of the variant haplotypes and the nucleotide changes at positions 387, 391, 392, and 622 (T to C) (Trp 208 Arg) were in linkage in another variant haplotype (21).…”
Section: Introductioncontrasting
confidence: 69%
“…Very recently, we found that Taiwanese differed from Caucasians and Japanese with respect to the allele frequencies of the UGT1A7 gene and the UGT1A7 * 4 (Asn 129 Arg 131 Arg 208 ) allele, with 0.017 in frequency in Caucasians (15), was not detected in our study subjects (21). We also observed that the functional polymorphisms at nucleotide 387 (T to G) (Asn 129 Lys) was associated with SNPs at nucleotides 391 (C to A) (Arg 131 Lys) and 392 (G to A) (Arg 131 Lys) in one of the variant haplotypes and the nucleotide changes at positions 387, 391, 392, and 622 (T to C) (Trp 208 Arg) were in linkage in another variant haplotype (21).…”
Section: Introductioncontrasting
confidence: 69%
“…Here we corroborated haplotype patterns and frequencies both within genes and between genes, and have established haplotypes across the entire UGT1A locus in a Caucasian and an Asian population. Previous reports investigated haplotype patterns for some of the UGT1As, either individually or in combination with other UGT1As (Lampe, et al, 1999;Guillemette, et al, 2000b;Ando, et al, 2002;Huang, et al, 2002;Saeki, et al, 2002;Villeneuve, et al, 2003;Girard, et al, 2004;Iwai, et al, 2004;Nagar, et al, 2004;Sai, et al, 2004;Verlaan, et al, 2004;Huang, et al, 2005;Innocenti, et al, 2005;Mori, et al, 2005;Saeki, et al, 2005a;Saeki, et al, 2005b;Saeki, et al, 2006). Decreasing LD with distance between UGT1A1 promoter polymorphisms was observed in African-Americans (Innocenti, et al, 2002;Maitland, et al, 2006) and differences in haplotype patterns in three ethnic groups were reported (Kaniwa, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwanese, carriage of the variant UGT1A1 gene at nt-211 (a risk factor of unconjugated hyperbilirubinemia) was found to be highly associated with the carriage of UGT1A7*3 allele [32]. UGT1A7*3 represents the allele that features the least benzopyrene (a carcinogen)-metabolite glucuronidation activity [33], and polymorphism in the UGT1A1 gene may cause decreased glucuronidation function for some carcinogens, such as estrogen [31], and therefore they are thought by a number of researchers to be risk factors for the development of cancers [31,33,34].…”
Section: Hereditary Unconjugated Hyperbilirubinemia and Cancer Suscepmentioning
confidence: 98%